2020
DOI: 10.20961/desa-kota.v2i1.31280.86-99
|View full text |Cite
|
Sign up to set email alerts
|

Perubahan Sentra Industri Kerajinan Batik Laweyan dalam Mendukung Kota Surakarta sebagai Kota Kreatif Desain

Abstract: <p>Kota Surakarta ditetapkan menjadi kota kreatif desain pada tahun 2013 oleh Kementrian Pariwisata dan Ekonomi Kreatif, dengan dibentuknya SCCN (Solo Creative City Network) untuk di ajukan ke UNESCO sebagai salah satu kota kreatif di Indonesia. Kota kreatif desain memfokuskan pada kegiatan industri kerajinan yang mengunakan desain untuk menciptakan sebuah karya. Kota kreatif desain memiliki komponen dasar yaitu ekonomi, lingkungan, dan komunitas kreatif. Di Kota Surakarta terdapat 21 industri kreatif ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Laweyan is known as the oldest batik industry center in Surakarta (Rachmanto et al, 2020), it has been observed since the production of batik for the upper class and nobility of the Pajang Kingdom and the Surakarta Kingdom around the 1500s (Anisah & Dharma Tohjiwa, 2016). In the cultural heritage of Indonesia, Batik is considered a high-quality art and is a part of ancient art forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laweyan is known as the oldest batik industry center in Surakarta (Rachmanto et al, 2020), it has been observed since the production of batik for the upper class and nobility of the Pajang Kingdom and the Surakarta Kingdom around the 1500s (Anisah & Dharma Tohjiwa, 2016). In the cultural heritage of Indonesia, Batik is considered a high-quality art and is a part of ancient art forms.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, we were spinning industry in 1800/1700, we were the thread industry".Laweyan is famous for its batik village because most of the Laweyan community has been producing batik up to now. Batik production in Laweyan is the oldest in Surakarta(Rachmanto et al, 2020). In 1997, Laweyan was declared as a cultural heritage area, tourist destination, and the oldest batik center in Surakarta because it has existed before the 15th century(Anisah & Dharma Tohjiwa, 2016).According to batik entrepreneur Pandono (44), in an interview on December 9, 2023, he said, "Yes, indeed, this village has been around since 1800.…”
mentioning
confidence: 99%